Unprecedented age-hardening and its structural requirement in a severely deformed Al-Cu-Mg alloy. (1st January 2022) - Yang, Ran; Feng, Zongqiang; Huang, Tianlin; Wu, Guilin; Godfrey, Andrew; Huang, Xiaoxu
Abstract: A gradient nanostructured surface layer was produced in an Al-Cu-Mg alloy (Al 2024) by means of a surface sliding friction treatment carried out at liquid nitrogen temperature. After aging treatment, unprecedented age-hardening was achieved at the surface layer, where microhardness values of >320 HV, more than twice that achievable by conventional precipitation hardening (150 HV), and well above the previously reported maximum value (280 HV) for this alloy, were achieved. Transmission electron microscopy and atom probe tomography analysis revealed that the formation of a nanograin structure at the deformed surface layer resulted in enhanced segregation of Cu and Mg during aging to narrowly spaced grain boundaries, with a corresponding suppression of precipitation. The enhanced grain boundary segregation instead of precipitation is considered to be responsible for the substantial age-hardening, although the underlying hardening mechanisms resulting from grain boundary segregation require further investigation. Graphical abstract: Image, graphical abstract